An electrophilic reagent for the synthesis of OCHFMe-containing molecules. Issue 20 (19th February 2018) - Carbonnel, Elodie; Pannecoucke, Xavier; Besset, Tatiana; Jubault, Philippe; Poisson, Thomas
Abstract : Herein the synthesis of a novel and bench stable electrophilic reagent to construct the OCFHMe motif from O -nucleophiles has been described. Abstract : Herein the synthesis of a novel and bench stable electrophilic reagent to construct the OCFHMe motif from O -nucleophiles has been described. This sulfonium salt, readily obtained in 5 steps, reacted with various phenols and alcohols. The resulting products, including complex molecules, were obtained in good yields. This reagent was also used for the functionalization of thiol derivatives.